Pengaruh Pengendalian Internal, Transparansi, Akuntabilitas, Dan Religiusitas Terhadap Pengelolaan Keuangan (Studi Kasus Pada Gereja Di Kecamatan Wonosalam Kabupaten Jombang) - Muhammad Taufiq Hidayat; Tabita Aprilia Nanda Mulyoko (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
This study is aimed to find internal control affects financial management, using transparency, accountability, and lack of religiosity as intervening variables. The population in this study were churches in Wonosalam District, which totaled 12 churches. The number of questionnaires distributed was 5 sets in 12 churches, but only 52 questionnaires were returned and could be processed.The testing technique uses the Statistical Package for the Social Sciences (SPSS) application by conducting validity tests, reliability tests, multiple linear tests, T-tests, and F-tests.Based on the test results, it shows that all variable has an effect on financial management;Based on the test results, it shows that: (1) Internal control has a positive effect on financial management;(2) Transparency has a positive effect on financial management; (3) Accountability has a positive effect on financial management; (4) Religiosity has a positive effect on financial managemen.